HUBUNGAN MODAL PSIKOLOGI DAN KINERJA GURU SMA NEGERI DI KABUPATEN PATI (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aims to determine the relationship of Capital Phisikologi and teacher performance high schools in Pati , Psikhogi Capital research that includes three-dimensional Optimism , Hope and Resiliency . As for the teacher 's performance is divided into Task Performance and Contextual Performance . The research was conducted on high school teachers in the State Pati as 183 people using proportional sampling . Statistical techniques were used to test validation , reliability test , the classic assumption test , correlation and regression testing . Based on the results of research known psychological dimensions of optimism and positive influence task performance significantly and have strong relationship closeness . Psychological optimistic and contextual performance and has a significant positive effect the relationship strong . While the dimensions of hope and the positive effect the relationship had a significant stronger good on task performance and contextual performance . While the dimensions Pychologi Resiliency and has a significant positive effect on the relationship strong and positive influence task performance significantly and have strong ties to the closeness of contextual performance at the State High School teacher Pati . Keywords : Optimism , Hope , Relisiency , Task Performance and Contextual Performance .